2009
DOI: 10.1007/s11270-009-0134-5
|View full text |Cite
|
Sign up to set email alerts
|

Nitro-PAHs and PAHs in Atmospheric Particulate Matters and Sea Sediments in Hiroshima Bay Area, Japan

Abstract: Atmospheric and sea sediment concentrations were measured for eight nitrated polycyclic aromatic hydrocarbons (nitro-PAHs) and three unsubstituted PAHs in a suburban area and sea sediments in the Hiroshima Bay watershed area, Japan, from July to December, 2006 (atmospheric particulate matter) and in September and November, 2004 (sea sediments). Atmospheric concentration was higher in winter than summer for both nitro-PAHs and PAHs. Concentrations in sea sediments were less than 10%, and pattern was similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 24 publications
1
22
0
3
Order By: Relevance
“…Several studies have reported NPAH concentrations in the low nanogram per gram range in both freshwater and marine sediments around the world [51,52], including our measurements in southern Lake Michigan sediments [49]. However, information regarding NPAH concentrations in aquatic biota is scarce.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported NPAH concentrations in the low nanogram per gram range in both freshwater and marine sediments around the world [51,52], including our measurements in southern Lake Michigan sediments [49]. However, information regarding NPAH concentrations in aquatic biota is scarce.…”
Section: Resultsmentioning
confidence: 99%
“…As derivatives of PAHs, NPAHs have been found in similar environmental compartments as PAHs (Ozaki et al, 2010; Perrini et al, 2005). They result from direct emissions from combustion sources as well as atmospheric transformations of PAHs (Perrini et al, 2005; Yaffe et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…They result from direct emissions from combustion sources as well as atmospheric transformations of PAHs (Perrini et al, 2005; Yaffe et al, 2001). Airborne NPAHs also can enter aquatic environments through atmospheric deposition and urban runoff (Ozaki et al, 2010). Although concentrations are far lower than levels of parent PAHs (Albinet et al, 2007; Khalek et al, 2011; Ozaki et al, 2010), NPAHs can have stronger carcinogenic and mutagenic activity (Schantz et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some nitro-PAHs have shown to be more mutagenic and carcinogenic than unsubstituted PAHs (Durant et al, 1996;Lewtas et al, 1990), and could be a significant fraction of direct-acting mutagenic compounds in the atmosphere (Kawanaka et al, 2008;Ozaki et al, 2010). Oxy-PAHs such as polycyclic aromatic quinones have been found to generate reactive oxygen species resulting in oxidative stress that can lead to allergic diseases (Chung et al, 2007;Sklorz et al, 2007), and polycyclic aromatic ketones, quinones and anhydrides are well known mutagenic compounds (Durant et al, 1996).…”
Section: Introductionmentioning
confidence: 99%